DNA methylation modules in airway smooth muscle are associated with asthma severity. Issue 4 (12th April 2018) - Perry, Mark M.; Lavender, Paul; Kuo, Chih-hsi Scott; Galea, Francesca; Michaeloudes, Charalambos; Flanagan, James M.; Fan Chung, Kian; Adcock, Ian M.
Asthma is a chronic airway inflammatory disorder characterised by airway hyperresponsiveness, inflammation and remodelling, including airway smooth muscle cell (ASMC) hyperplasia and subepithelial airway fibrosis [1, 2]. ASMCs from severe asthmatics are hyperproliferative, release more pro-inflammatory cytokines and are corticosteroid-insensitive compared with those from healthy individuals and non-severe asthma patients [3, 4]. Genetic and epigenetic processes such as miRNA expression and DNA methylation have been implicated in asthma pathogenesis [5]. Indeed, DNA methylation is altered in asthmatic blood cells [5] and may be a biomarker of atopy [6]. Abnormal DNA methylation patterns distinguish airway smooth muscle cell function in asthma and asthma severity http://ow.ly/cTrK30iCwVK